Changes in external load when modifying rules of 5-on-5 scrimmage situations in elite basketball - Vazquez-Guerrero, J.; Reche, X.; Cos, F.; Casamichana, D.; Sampaio, J. (The Journal of Strength and Conditioning Research, 2020)
Constraining tasks are very frequent during the team sports training process; however, most of the effects of these coaching decisions are unknown, which leads to less controlled performing environments, with less chances to promote improvements. The aim of this study was to determine the effects of modifying rules of 5-a-side scrimmage on the physical performance of professional basketball players. Data were collected from 12 elite male players (age, 29.6 ± 4.5 years; height, 1.99 ± 9.6 cm; body mass, 92.1 ± 11.9 kg) from the Spanish first Division of Basketball during thirty-three 5-on-5 scrimmage situations over a 18-week period. Physical demands were assessed using WIMU PRO Local Positioning System (Realtrack Systems, Almeria, Spain) and included total and speed-ranged distance covered, player load, peak speed, number of high-intensity actions, number of total and high-intensity accelerations and decelerations, and peak acceleration. A repeated-measures analysis of variance was used to test the differences in all variables, considering playing in half-court (HALF), half-court and transition (HTRAN), and full-court (FULL) conditions for the 5-on-5 scrimmage drill. Results showed that during the HALF condition, there was less distance covered (effect size [ES] = 3.55), lower peak speeds (ES = 3.00), less player load (ES = 2.79), lesser number of high-intensity actions (ES = 1.45), and lesser number of high-intensity accelerations (ES = 1.44) and decelerations (ES = 1.31) than in FULL. In HTRAN, players covered more distance (ES = 2.42), presented higher player load (ES = 1.88), higher intensity actions (ES = 1.02), and peak speed (ES = 4.22) than in HALF. In conclusion, physical demands can be modulated changing the rules and court size using 5-on-5 scrimmage situations, and this factor should be taken into account when designing training drills and when fine-tuning periodization.